Investigation of three-dimensional forces during additive friction stir deposition — How could force signals reveal the deposition quality? - Huang, Yiming; Liu, Qi; Zhang, Kaiyue; Li, Mingyu; Yang, Tianhao; Yang, Lijun; Cui, Lei (International journal of machine tools & manufacture, 2025)
Additive friction stir deposition (AFSD) is a solid-phase forming technology based on microzone forging, which is essentially a force-driven additive manufacturing process. This work focuses on the effects of the AFSD parameters on the force signals and forming quality, which is highly important for optimizing the process parameters and controlling the forming quality. By analyzing the force features in the time‒frequency domain, the evolution mechanism of three-dimensional forces during AFSD was explored. A 3D scanner, scanning electron microscope (SEM) and electron backscatter diffraction (EBSD) were used to clarify the surface morphology and microstructures of the deposition layers. It was found that deposition defects were accompanied by a lack of plasticization or nonuniform deformation between the advancing side (AS) and the retreating side (RS). Moreover, the relationships among the process parameters, three-dimensional forces and deposition quality were investigated. It is proved that force signal can effectively reflect the deposition quality. A comprehensive prediction model based on three-dimensional force features was developed, achieving an accurate prediction of deposition quality. Furthermore, this work demonstrated the feasibility of AFSD quality control on the basis of force signals. The currently employed control strategies can be further extended to address the AFSD of large components in the future. [Display omitted] •Evolution mechanism of three-dimensional forces during additive friction stir deposition.•Effects of process parameters on the quality of single-layer and multilayer deposition.•This study proves force features can reflect the deposition quality effectively.•Proposing the force-based prediction and control method to improve forming quality.